Digital Transformation of Land Services Through Management In-formation Systems: Case Study of BPN Asahan Regency - Rizqiya Adha Riani; Dewi Dewi; Balqis Amanda; Ade Khairani Hasibuan; Fatma Sari; Dailami Dailami (Pusat Riset dan Inovasi Nasional, 2025)
Digital transformation of public services is an important step towards efficient, transparent and accountable government institutions. This study recommends strengthening digital infrastructure and providing ongoing training for staff and the community to support the optimization of digital transformation of land services. The purpose of this study is to analyze the implementation of Management Information Systems in supporting the digital transformation of land services at the Land Office (BPN) of Asahan Regency. The study used a qualitative approach, combining case studies and analysis. The results show that various services such as Complete System Land Registration (PTSL), certificate checking, and electronic transfer of rights have been digitized, supported by innovations such as the Touch My Land application and digitization of land registration archives. This shift has accelerated service processes, increased transparency, and improved public satisfaction. However, challenges remain in terms of public digital literacy, technology infrastructure, data security, and so on. To maintain the sustainability of the transformation, Asahan District BPN implements a strategy of continuous system development, human resource training, and cross-sector collaboration.